Corporate response to Black Lives Matter - Elias, Jaan; Katic, Ivana V. (London : Yale School of Management, 2021)
Millions of Americans protested George Floyd's death while in police custody in the late spring of 2020. Black Lives Matter became the protesters' catchphrase as they demanded greater racial fairness in American culture. The protests spread across the nation, drawing demonstrators from all over the world to both tiny villages and big cities. The three weeks of protests and marches that followed Floyd's death were dubbed the biggest social movement in American history by many commentators.Corporations typically avoided participating in significant social movements, especially those without a clear economic focus. But in the instance of the Black Lives Matter demonstrations, many businesses and their executives showed their support for the protesters and the goal of racial fairness. Such corporate support for a social movement was unusual. Many people questioned whether more powerful stakeholder groups including consumers, employees, and investors may have played a role in this instance of corporate activism.Both the left and the right lambasted these businesses for their "conscious capitalism" and their hypocrisy in response to this show of corporate cooperation. Could the opponents of corporate participation stifle whatever gains that businesses made from adopting positions that won over other stakeholders? Given the history of diversity and equity at many firms, how reliable were corporate statements?Along with showing their support, numerous firms also promised to provide money to a range of groups working to achieve more racial justice. Additionally, promises to change some policies and work toward increasing diversity in corporate levels were made. A select few businesses have made significant commitments to advance Black people's business interests through targeted initiatives that support Black business development and wealth accumulation.But two years on, observers wondered how much difference had the corporate support made toward solving the problems at w
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Diversity in the workplace -- Case studies; Organizational behavior -- Case studies